Assessment of Cerebrovascular Resistance with Model of Cerebrovascular Pressure Transmission - Narayanan, Nithya (2008)
A two step modeling method of cerebrovascular pressure transmission, the dynamic relationship between arterial blood pressure (ABP) and intracranial pressure (ICP) has been developed as a means to continuously assess cerebrovascular regulation and resistance. Initially, system identification modeling was used to construct a numerical model of cerebrovascular pressure transmission. Next, the modal frequencies of the numerical model and the actual ABP recording were used to manipulate the parameters of a physiologically-based biomechanical model such that: 1) the actual and simulated ICP; and 2) the numerical and biomechanical model modal frequencies match. This study was designed to compare changes of cerebrovascular resistance of the biomechanical model with the expected changes of cerebrovascular resistance associated with the occurrence of either a plateau wave or refractory intracranial hypertension. Pressure recordings from five patients with plateau waves and five patients with intracranial hypertension were used. Vascular resistance decreased significantly during the plateau wave and was inversely related to CPP, indicating active vasoreactivity. In contrast, vascular resistance increased significantly during intractable intracranial hypertension and was directly related to CPP, indicating impaired cerebrovascular regulation. Such results support the use of the modeling method as a means to continuously assess changes of cerebrovascular regulation and resistance.